Antimicrobial Activities of Leaves Extracts of Mistol (Ziziphusmistol), Algarrobo blanco (Prosopisalba) and Tusca (Acacia Aroma) to be Applied to Meat Products Preservation - Ruiz, Silvana Cecilia (2017)
The aim of the present study is to analyze the in vitro antioxidant activity against pathogens such as Salmonella, Staphylococcus aureus, Staphylococcus sp, Bacillus cereus, Micrococcus, Escherichia coli and Listeria innocua using Ziziphus mistol (Mistol), Prosopis alba (Algarrobo blanco) and Acacia aroma (Tusca) extracts with 70% acetone and 50% ethanol as solvents extraction as antibacterial. Determination was made by agar disk diffusion method. All the extracts showed some antibacterial activity, however, Bacillus cereus was more resistant and Staphylococcus aureus was more sensitive to the extracts evaluated in comparison with the other strains of bacteria used in the test. Nevertheless, Algarrobo blanco extracts in 50% ethanol significantly inhibited the growth of Staphylococcus sp. Therefore, extracts Mistol, Algarrobo blanco and Tusca could have potential as natural preservatives for fresh meat products.